Usaha Malsindo Trilateral Coordinated Patrol dalam Menangani Perampokan Bersenjata di Selat Malaka - Indriani Wijaya, Sri Magfirah; Utomo, Tri Cahyo; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The strategic location of the Strait of Malacca makes it one of the busiest straits in the world. The Malacca Strait serves as a channel for the distribution of oil and natural gas as a need for energy security and world trade commodities through the sea. But the high activity in the Strait is not balanced with security guarantees. Therefore, the cooperation of coastal countries is needed to maintain the security of the waters around the Strait of Malacca. Indonesia, Malaysia and Singapore formed cooperation to handle armed robbery in Malacca Strait in 2004 named Malsindo. The type of this research is analytic describtive using qualitative method to apply neoliberalism theory. This research is aimed to know the reason measures to combat armed robbery cases in Malacca Strait between 2004-2013. The result of this research finds that measures taken by coastal country to combat armed robbery consists of Malacca Strait Sea Patrol (MSP) which was launched in 2004, Eyes in The Sky (EIS) which was launched in 2005 and MSP-IS in 2006.